Green Masquerade: Neo-liberalism, Extractive Renewable Energy Transitions, and the ‘Good’ Anthropocene in South Africa - Michelle Pressend (Revue Internationale de Politique de Développement)
This chapter examines the ‘green’ energy developments apparent in the South African government’s energy policy and renewable energy programme. In 2011, the South African government introduced the Renewable Energy Independent Power Producer Procurement Programme as a new policy imperative for electricity generation from renewable energy sources through publicprivate partnerships. The Programme has been hailed for attracting a huge amount of direct foreign investment in climate mitigation in South Africa. This chapter analyses the material nature of the Programme and the publicprivate partnership investment conditions, based on a case study of the Tsitsikamma Community Wind Farm in the Eastern Cape in South Africa, an electricity generation project initiated prior to the introduction of the Independent Power Producer renewable energy programme on community reclaimed land. This community was a willing partner in the wind energy investment partnership. Despite their inclusion in this techno-capitalist development project, however, the material well-being of members of this community remains unchanged, as does the degraded state of the commercial agricultural land involved. The chapter argues that the capitalist neo-liberal logic of alternative ‘green’ energy interventions in investment models such as this renewable energy programme is embedded in the machinations of the extractivist productivist model through ‘new’ forms of financialisaton for capital accumulation.